2018
DOI: 10.1371/journal.pmed.1002705
|View full text |Cite
|
Sign up to set email alerts
|

Mobile detection of autism through machine learning on home video: A development and prospective validation study

Abstract: BackgroundThe standard approaches to diagnosing autism spectrum disorder (ASD) evaluate between 20 and 100 behaviors and take several hours to complete. This has in part contributed to long wait times for a diagnosis and subsequent delays in access to therapy. We hypothesize that the use of machine learning analysis on home video can speed the diagnosis without compromising accuracy. We have analyzed item-level records from 2 standard diagnostic instruments to construct machine learning classifiers optimized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(189 citation statements)
references
References 36 publications
(50 reference statements)
2
176
0
Order By: Relevance
“…all subtasks) and consequently the time saved by coding only a smaller number of behavioral features is marginal. In contrast to this view, however, recent findings have shown that ASD classification of children can be achieved by applying the ADOS items to shorter, unstructured social interactions [54][55][56] and even by relying solely on written extracts of children´s medical and educational records 57,58 , thereby suggesting that a reduction in time associated with ASD detection might be feasible. For example, Fusaro and colleagues 54 have assessed the feasibility of applying all of the ADOS Module 1 codes, but not the behavior observation exam, to short (<10 minutes) and unstructured home-videos collected from YouTube.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…all subtasks) and consequently the time saved by coding only a smaller number of behavioral features is marginal. In contrast to this view, however, recent findings have shown that ASD classification of children can be achieved by applying the ADOS items to shorter, unstructured social interactions [54][55][56] and even by relying solely on written extracts of children´s medical and educational records 57,58 , thereby suggesting that a reduction in time associated with ASD detection might be feasible. For example, Fusaro and colleagues 54 have assessed the feasibility of applying all of the ADOS Module 1 codes, but not the behavior observation exam, to short (<10 minutes) and unstructured home-videos collected from YouTube.…”
Section: Discussionmentioning
confidence: 96%
“…These findings suggest that short, unstructured interactions can provide sufficient information to rate ADOS codes and to detect ASD. Building upon this work, Tariq and colleagues 55 recently investigated how the reduced feature subsets from the ADOS modules 1 to 3 that were identified in previous machine learning experiments 38,41,42 could be translated into clinical practice. For this purpose, they created a mobile web portal and asked video raters to assess the previously identified minimal feature subsets in short home videos (<5 minutes) of children with and without ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, we have, strictly speaking, found a candidate referral tool for child development specialists examining young pre-walking infants. Once having proved the replicability of this prodrome, machine learning classification using the relevant features could be extracted from videos of infants taken in an unforeseen natural environment, alerting for ASD risk in minutes (Tariq et al, 2018(Tariq et al, , 2019.…”
Section: Early Signs Of Autism?mentioning
confidence: 99%
“…Third, there remains a lack of clear understanding of the technique that is being used. A number of studies used multiple algorithm approaches and report on the highest predictive value [32,33,36,37,43,44,48,49]. Before arguing on the best algorithm to use, it would be important to understand why there are such differences in the results and the reason as to which approach would be most appropriate depending on the characteristics of the dataset and what sort of an output one is trying to achieve.…”
Section: Discussionmentioning
confidence: 99%